2002
DOI: 10.1021/bi025958g
|View full text |Cite
|
Sign up to set email alerts
|

Protease-Sensitive Scrapie Prion Protein in Aggregates of Heterogeneous Sizes

Abstract: The pathological prion protein PrP(Sc) is the only known component of the infectious prion. In cells infected with prions, PrP(Sc) is formed posttranslationally by the refolding of the benign cell surface glycoprotein PrP(C) into an aberrant conformation. The two PrP isoforms possess very different properties, as PrP(Sc) has a protease-resistant core, forms very large amyloidic aggregates in detergents, and is only weakly immunoreactive in its native form. We now show that prion-infected rodent brains and cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
83
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(91 citation statements)
references
References 45 publications
7
83
1
Order By: Relevance
“…In scrapie-infected hamsters, PK-sensitive PrP Sc molecules from low-molecular-weight aggregates are made up of fewer PrP units (i.e., are smaller) than PK-resistant PrP Sc aggregates (46,47). Combining these observations with our own results, we hypothesize that the smaller average seed particle size of PK-sensitive PrP Sc may result in slower RT-QuIC kinetics and lead to lower AFRs and longer lag times.…”
Section: Discussionsupporting
confidence: 67%
“…In scrapie-infected hamsters, PK-sensitive PrP Sc molecules from low-molecular-weight aggregates are made up of fewer PrP units (i.e., are smaller) than PK-resistant PrP Sc aggregates (46,47). Combining these observations with our own results, we hypothesize that the smaller average seed particle size of PK-sensitive PrP Sc may result in slower RT-QuIC kinetics and lead to lower AFRs and longer lag times.…”
Section: Discussionsupporting
confidence: 67%
“…The S1 fractions prepared by centrifugation of 20% brain homogenates at 8,000 ϫ g for 5 min at 4°C were incubated with an equal volume of 2% sarcosyl for 30 min on ice. Samples were loaded atop a 10 to 60% step sucrose gradient and centrifuged at 200,000 ϫ g for 1 h at 4°C, as described by Tzaban et al (39). Eleven fractions were collected from the top of the tube and processed for Western blot analysis of PrP.…”
Section: Novel Cjd Prion Strainmentioning
confidence: 99%
“…For example, it is largely believed that the heterogeneity in the fragment profile of proteinase K (PK)-digested PrP Sc , which distinguishes at least some of the known prion strains, is the direct consequence of PrP Sc aggregates having distinct conformations (17)(18)(19)(20)(21). Similarly, sedimentation profiles and protease sensitivity have been used as indirect markers of PrP Sc structure and have shown a correlation with strain-specific transmission properties (22)(23)(24)(25)(26)(27). More recently, studies with rodent-adapted, cloned prion strains demonstrated that also the conformational stability of PrP Sc , measured indirectly either by inducing a progressive denaturation of the protein with the chaotropic salt guanidine hydrochloride (GdnHCl) or by exposing the protein to increasing temperatures in the presence of sodium dodecyl sulfate (SDS), may vary among different strains (28)(29)(30).…”
mentioning
confidence: 99%